(untitled) (Experimental biology, 2024)
The cytogenetic research reveals the radiosensitivity of plant test system Allium cepa in comparison to the traditional test system in the form of human peripheral blood lymphocytes culture. For the work, it was carried out an assessment of cytogenetic damage caused by short-term external irradiation in the range of low doses 0.01–0.7 Gy. The study indicated the high induction sensitivity of the Allium test for cytogenetic effects on the meristematic cells of onion roots. The most hypersensitive response to ionizing radiation is demonstrated by the induction of micronuclei in interphase cells. It’s shown a positive correlation between the frequency of chromosomal abnormalities in lymphocytes and micronuclei in interphase cells (+0.87), as well as the frequency of chromosomal abnormalities in metaphases of lymphocytes and onion roots (+0.93). The results obtained confirm the possibility of using the Allium cepa as a suitable test system for the primary biological determination of genotoxicity arising from external exposure to γ-radiation.